Achieving efficient thick active layer and large area ternary polymer solar cells by incorporating a new fused heptacyclic non-fullerene acceptor. Issue 41 (11th October 2018) - Yin, Pan; Zheng, Tao; Wu, Yue; Liu, Gangjian; Zhang, Zhi-Guo; Cui, Chaohua; Li, Yongfang; Shen, Ping
Abstract : A ternary PSC was constructed and exhibited a high PCE of 10.41% with a thicker film and a large area. Abstract : Nowadays, constructing ternary polymer solar cells (PSCs) and developing non-fullerene acceptors (NFAs) have emerged as two powerful and efficient means to propel the device efficiency further forward. However, the incorporation of NFAs into a fullerene-based binary PSC to form high-performance donor : fullerene : NFA type ternary PSCs with a thick active layer and large area is still a challenge due to their inferior charge transport properties, complicated blend morphology and unclear aggregation behavior. In this contribution, a new low bandgap NFA (DTCFOIC) based on a fused heptacyclic core (dithienocyclopentafluorene) is developed and blended with a medium bandgap polymer donor PBDB-T to form a binary PSC achieving a power conversion efficiency (PCE) of 6.92%. When a small amount of DTCFOIC was employed as the additional acceptor combined with fullerene-based PC71 BM to construct the PBDB-T : PC71 BM : DTCFOIC ternary PSCs, an enhanced PCE of 9.40% was obtained after carefully optimizing the blend composition and the amount of the additive 1, 8-diiodooctane (DIO) with a thin active layer (100 nm) and normal area (0.04 cm 2 ). This could be mainly attributed to the extended absorption range, improved charge transfer, dissociation and collection properties, and suppressed charge recombination as well as optimized blend morphology in the ternary blend after the addition of NFA and DIO. Moreover, the photovoltaic performance of the ternary PSCs could be further optimized to achieve a higher PCE of 10.13% with a thicker active layer (160 nm) and eventually the highest PCE of 10.41% can be achieved with a thick active layer of 190 nm and a large area of 0.1 cm 2, which is among the highest efficiencies of both thick layer and large area ternary PSCs. Besides, the ternary PSCs preserved a high PCE over 9% even with a larger active area of 1 cm 2 using a thick active layer (172 nm). This observation demonstrates that incorporating a NFA to construct donor : fullerene : NFA type ternary PSCs is a feasible and effective approach to significantly enhance the performance of the resulting ternary system. Meanwhile, our results related to the thick active layer and large area suggest that this ternary system has a promising application prospect for mass manufacturing high-performance PSCs with a roll-to-roll process.